2019
DOI: 10.31234/osf.io/9t4dp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early childhood technoference threat is predicted by authoritative parenting, but not parental knowledge of digital risks.

Abstract: Frequent disruption to parent-child interactions by technology (technoference) significantly impacts problematic behaviours and socioemotional development. Currently unknown is whether this is a novel challenge presented to all parents by the proliferation of technology, or representative of existing maladaptive parenting practices. Two- hundred and fifteen UK parents (Mage = 36 years) self-reported parenting style (i.e., authoritative, authoritarian, permissive), technoference, problematic technology use, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We advise exploration of the role of family members' norms and attitudes linked to technology use, as well as the role of different parenting styles and different family compositions. Turvill et al (2019), for example, found that technoference prevalence disproportionately threatens a subset of children, depending on the technology use and parenting style of their parents. This finding suggests that parental smartphone use patterns may be symptomatic for broader parenting styles, possibly resulting in cumulated or aggravated negative outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…We advise exploration of the role of family members' norms and attitudes linked to technology use, as well as the role of different parenting styles and different family compositions. Turvill et al (2019), for example, found that technoference prevalence disproportionately threatens a subset of children, depending on the technology use and parenting style of their parents. This finding suggests that parental smartphone use patterns may be symptomatic for broader parenting styles, possibly resulting in cumulated or aggravated negative outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…These parents do not explicitly limit their children's behaviour but expect them to be responsible and self-regulating. They adhere to the rule of thumb -for example, when it comes to Internet time (Konok et al 2020;Turvill et al 2019).…”
Section: Adaptation Of Digital Parenting During Pandemicmentioning
confidence: 99%
“…Pattern foster resilience in terms of early childhood should not let children free without understanding the principles of cause and effect. This is also the reason for parents to apply Authoritative Parenting [8] as parenting style in the Age of disruption in Early Childhood as stated by 16 parents with educational background in Tahir, aged 25-40 years Characteristics of patient and wise. Set limits, give an understanding to the children, and responsive to their emotional needs are three principal things in their parenting style.…”
Section: A Set Limits Give An Understanding To the Children And Respo...mentioning
confidence: 99%